2012
DOI: 10.4168/aair.2012.4.3.122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asthma Epidemiology on the Risk for Other Diseases

Abstract: Asthma is a multifactorial chronic disease affecting a significant proportion of people in the United States and worldwide. Numerous laboratory and epidemiological studies have attempted to understand the etiology and underlying mechanisms of asthma and to identify effective therapies. However, the impact of asthma on the risk for other diseases has drawn little attention. This paper discusses the potential effects of asthma as a risk factor for other diseases, explores the potential mechanisms, and reviews th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 82 publications
(81 reference statements)
1
17
0
1
Order By: Relevance
“…In our study, the highest incidence rate ratio was observed in children up to 10 years old for the asthma cohort and in adults aged 50-59 years old for the COPD cohort, where the incidence of Crohn's disease was more than double that in the general population. The findings of VIRTA et al [8] were also suggestive of an association between childhood asthma and Crohn's disease, while two other studies failed to find a significant association [28,29].…”
Section: Discussionmentioning
confidence: 90%
“…In our study, the highest incidence rate ratio was observed in children up to 10 years old for the asthma cohort and in adults aged 50-59 years old for the COPD cohort, where the incidence of Crohn's disease was more than double that in the general population. The findings of VIRTA et al [8] were also suggestive of an association between childhood asthma and Crohn's disease, while two other studies failed to find a significant association [28,29].…”
Section: Discussionmentioning
confidence: 90%
“…Asthmatics may have increased susceptibility for H1N1pdm infection [45], possibly because of alterations in the airway architecture [46], [47] and impairment of innate immunity [47]. Another hypothesis to explain a higher GMT in subjects with such medical conditions, regardless of their susceptibility to infection, would be a more severe illness [48] involving a greater immune response [49].…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential causal relationships between atopic conditions and microbial infections or colonization: protective (eg, the “hygiene hypothesis”), 22,23 provocative (eg, rhinovirus or bacterial colonization), 24,25 and contextual effects (eg, the microbiome hypothesis), 26,27 as well as reverse causality 20,28-30 (Figure 1). This paper focuses on the effect of atopic conditions on the risk of infections, termed reverse causality .…”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionsmentioning
confidence: 99%